Scientific Attitude of Young Children through Literature and Project-Based Learning Organization - Veena Prachagool, (Journal of Educational Issues, 2024)
Young children’s scientific attitude is a basic norm of human kind to cultivated actual learning which has been an expected to be a curious, motivated, generous and responsible person. The study aims to investigate scientific attitude of young children through literature-based and project-based learning organization (LPBL). Participants were 25 of young children, age 5-6 years from Mahasarakham University Demonstration School (Elementary), Thailand. The duration of experiment was 8 weeks, 4 days a week and 90 minutes per day that was 32 times. The research instruments were 32 LPBL learning plans, learning behavior observation forms, scientific attitude inventory, and debriefing focuses group interviews. The statistics used in the study were average and standard deviation. The results showed that young children have scientific attitudes was at high level by means of LPBL learning organization. The qualitative data supported that they express scientific attitude accordance with nature of learning.